Study on the Coupled Dynamic Evolution of Social Entrepreneurship and Rural Labor Return in the Context of Rural Revitalization - Lu, Shuo; Zhang, Xiumei; Shi, Jianan; Guo, Yanping; Lu, Jiayi (Transactions on Economics, Business and Management Research, 2024)
Based on the panel data of social entrepreneurship and rural labor force return in 31 provinces and municipalities in China from 2016-2021, this paper constructs the evaluation system of entrepreneurial activity from the perspective of rural revitalization, and empirically analyzes it by using entropy weighting method, coupled coordination degree model, and relative development degree model to explore the development level of the two elements. The results show that: at the time level, the return of rural labor force and social entrepreneurship activity in 31 provinces in China from 2016 to 2021 tend to develop in a generally coordinated manner, and the level of coordinated development of the two factors fluctuates and rises; the degree of coupling and coordination of the two factors in general shows a "W"-type cyclical fluctuation characteristic.